Analysis of Banua Berkah Tsunami Business Revenue as Guided by the Kanwil DJPB Central sulawesi - Dini Angraini; Santi Yunus; Yunus Sading; Rita Yunus; Meity Ferdiana Paskual (ProBisnis : Jurnal Manajemen, 2024)
Banua Berkah Tsunami is a business that produces banana chips, fried onions and tuna floss. This research aims to analyze the income and feasibility of the Banua Berkah Tsunami business under the guidance of the Ministry of Finance of Palu City. The data analysis method used is an income analysis formula consisting of TC, TR, and π (profit). Meanwhile, to calculate business feasibility, use the Revenue Cost Ratio (R/C Ratio) formula. The research results show that the average income from the Banua Berkah Tsunami business is IDR 5,750,000/month with production costs incurred of IDR 4,285,423/month. These production costs consist of fixed costs of IDR 141,173/month and variable costs of IDR 4,144,250/month. From the results of data analysis, it was found that the income obtained from the Banua Berkah Tsunami business was IDR 1,464,577/month. Based on the calculation of business feasibility (R/C Ratio), a value (R/C Ratio) of 1.34 or 1.34>1 is obtained, meaning that for every cost incurred Rp. So it can be concluded that the Banua Berkah Tsunami business can be said to be profitable and worth running